A method to design and manufacture low-cost patient-specific templates for spinal surgery: evaluation of multiple additive manufacturing methods. Issue 4 (30th November 2018) - Rutkowski, David R; Sun, Derrick; Anderson, Paul A; Roldán-Alzate, Alejandro
Aim: This study aims to detail an interactive process to design, fabricate and test patient-specific drill templates and surgical training models, and to determine the advantages and disadvantages of multiple low-cost additive manufacturing methods in this application.Materials & methods: Image data from one patient were used to develop and manufacture both patient-specific drill templates for spinal surgery and replica spine models for surgical training with three, low-cost additive manufacturing methods. With the input of an orthopedic surgeon, the models were analyzed based on function, production time, cost, durability and appearance.Results & conclusion: Although differences were observed in the spinal surgery training models, the performance of the drill template models showed little variance across fabrication methods and template materials.